2017
DOI: 10.1038/s41598-017-06514-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dipeptidyl-peptidase-4 activity is associated with left ventricular systolic function in patients with ST-segment elevation myocardial infarction

Abstract: Plasma dipeptidyl-peptidase-4 activity (DPP4a) is inversely associated with left ventricular function in patients with heart failure (HF) or diabetes. However, the association between DPP4a and left ventricular function in ST-segment elevation myocardial infarction (STEMI) patients has not been reported. We studied this association in 584 consecutive STEMI patients at a tertiary referral center from July 2014 to October 2015. DPP4a and plasma N-terminal prohormone of B-type natriuretic peptide (NT-proBNP) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…However, in our study cohort, no significant correlation was detected between BMI and serum DPP4 activity. This is in accordance with previous findings in STEMI patients, in whom no difference was detected in BMI among different quartiles of plasma DPP4 activity 39 , 54 . In contrast, as mentioned earlier, patients with a recent myocardial infarction exhibited a significantly reduced pre-operative DDP4 activity when compared to patients without recent infarction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in our study cohort, no significant correlation was detected between BMI and serum DPP4 activity. This is in accordance with previous findings in STEMI patients, in whom no difference was detected in BMI among different quartiles of plasma DPP4 activity 39 , 54 . In contrast, as mentioned earlier, patients with a recent myocardial infarction exhibited a significantly reduced pre-operative DDP4 activity when compared to patients without recent infarction.…”
Section: Discussionsupporting
confidence: 93%
“…The latter became also obvious in a recent study by Li et al . demonstrating low plasma DPP4 activity to be independently associated with left ventricular systolic dysfunction in patients with ST-segment elevation myocardial infarction (STEMI) 39 . These findings are in line with our study reporting low post-operative DPP4 activity to be associated with a worse patient outcome after cardiac surgery, while the myocardial I/R injury following surgery may be in analogy to STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although there was no difference in cardiac function between the groups, sitagliptin significantly decreased LVEF and %FS from baseline to 12 weeks. Similarly, Mulvihill et al demonstrated that a DPP-4 inhibitor impaired cardiac function in a rodent model [ 49 ] and Li et al reported that DPP-4 activity was positively correlated with LV systolic function, suggesting that DPP-4 inhibition is correlated with LV systolic dysfunction in humans [ 50 ]. Furthermore, various CVD outcome trials have indicated that DPP-4 inhibitors increase the risk of hospitalizations due to heart failure [ 9 , 51 ].…”
Section: Discussionmentioning
confidence: 99%